Creating design methods for the page header and its links for Arab newspapers (Journal of the College of Basic Education, 2022)
The head of the page is considered one of the important visual foci, as the reader's eye falls directly on it and forms an areaThe important and first visual polarization on the page, in addition to the importance of its design, especially (The banner) as it prepares the distinctive identity for each newspaper.It has been customary to design the headers of Arab and Iraqi newspapers in a traditional style.It is typical in the process of distributing the units of the page's head, which includes (the banner, the ears, and the neck) and does not implyThe way these units are organized and the relationships between them are used, which leads to a weakness of the creativity process.and innovation in it and which